(untitled) (Global Journal of Human-Social Science, 2025)
This paper reflects on the interconnections between socio-spatial justice theories and housing policies implemented in Brazil over recent decades. Drawing from key works that address the concept of justice in and for geography, we conduct a critical review to analyze the trajectory of Brazilian housing policy. The study highlights potential elements for rethinking strategies and proposals aimed at fostering more equitable cities.